Influence of Sucrose and Silver Nitrate to Ameliorate Post Harvest Performance of Gladiolus Spikes - Khan, Achak; Ahmad, Masood; Muhammad Arif; Ali, Hamza; Jabin, Shahana; Awan, Muhammad Talha; Khattak, Muhammad Reshteen; Khalil, Ibadullah; Syed Razaullah; Abu Sufyan; Khan, Zakir; Muhammad Abbas (Indus Journal of Bioscience Research, 2024)
The present study on “Influence of sucrose and silver nitrate to ameliorate post-harvest performance of gladiolus spikes” was conducted at Horticultural Lab., The University of Agriculture Peshawar during the year 2021. The experiment was carried out in Complete Randomized Design. There were nine treatments which were replicated three times. These treatments include Control (0), AgNO3 (0.03 g/L), AgNO3 (0.05 g/L), sucrose (40 g/L), sucrose (60 g/L), AgNO3+ Sucrose (0.03 g/L + 40 g/L), AgNO3+ sucrose (0.03 g/L+ 60 g/L), AgNO3 + sucrose (0.05 g/L+40 g/L) and AgNO3 + sucrose (0.05 g/L+60 g/L). Silver nitrate and sucrose significantly affected all the parameters. The mean value of silver nitrate and sucrose showed that cut flowers of gladiolus placed in holding solution of AgNO3 + Sucrose (0.05 g/L + 60 g/L) results in maximum days to opening of 1st floret (3.90), opening of full spike (8), fading of 1st floret (8.66), fading of full spike (23), fresh floret weight (6.36 g), senesced floret weight (0.96 g), reducing sugar (12.83 mg g-1), non-reducing sugar (15.93 mg g-1), total phenolic content (0.63 mg g-1) with minimum electrolyte leakage (63.03%) and maximum vase life (15.33 days) and proved superior as compared to other treatments. It is concluded from the results that application of AgNO3 + Sucrose (0.05 g/L + 60 g/L) in holding solution was most effective to retain the quality of gladiolus floret and spike over extended period and to enhance the vase life of gladiolus cut spikes. However, it was statistically similar to the effect of 0.05 g/L + 40 g/L (AgNO3 + Sucrose) for most of the studied attributes.